The African State under Globalisation: Security, Transnational Corporations, and the Environment - Egbe, Olawari D. J.; Ibani, Bubarayi G. (University of Nigeria Journal of Political Economy, 2021)
The 21st century is and remains principally an era of globalisation. As good as this whole idea of globalisation phonetically sounds, all facets of globalisation—from economic, social, political, to cultural dimensions of it—are not fascinating but gloomy for the state in the global South, especially Africa. A particular context where the Africa state has suffered enormous stress is its environment. Thus, this paper worried by this simply question: Why is the environment in Africa so plundered and impoverished? The paper asserts that the principal explanation for such a gloomy state of the environment in Africa under globalisation is that a corporate octopus, the Transnational Corporation (TNC), whose economic fortunes dwarf most African states is and remains the principal foot-soldier of globalisation that helps to wreak havoc on the environment in Africa. The paper, essentially being qualitative, discovers that in a century of globalisation dominated by TNCs, the state in Africa and its environment stands dwarfed in all of globalisation’s numerous facets, mostly the economic domain where the environment of resource-rich indigenous peoples suffers from incalculable burdens in course of exploration/mining, exploitation, transportation, gas flaring and storage. The paper concludes in agreeing that whereas globalisation and the Breton Wood institutions (the World Bank, the International Monetary Fund, and the World Trade Centre) work in concert and so are relevant in the prevailing economic order, a reformed World Bank in the typology of an International Asset Agency (IAA) that will ensure equity and ecological balance in global economic relations, especially in relations to Africa’s environmental needs be evolved.